Dual African origins of global Aedes aegypti s.l. populations revealed by mitochondrial DNA. - Michelle Moore; Massamba Sylla; Laura Goss; Marion Warigia Burugu; Rosemary Sang; Luna W Kamau; Eucharia Unoma Kenya; Chris Bosio; Maria de Lourdes Munoz; Maria Sharakova; William Cormack Black (Public Library of Science (PLoS), 2013)
Aedes aegypti is the primary global vector to humans of yellow fever and dengue flaviviruses. Over the past 50 years, many population genetic studies have documented large genetic differences among global populations of this species. These studies initially used morphological polymorphisms, followed later by allozymes, and most recently various molecular genetic markers including microsatellites and mitochondrial markers. In particular, since 2000, fourteen publications and four unpublished datasets have used sequence data from the NADH dehydrogenase subunit 4 mitochondrial gene to compare Ae. aegypti collections and collectively 95 unique mtDNA haplotypes have been found. Phylogenetic analyses in these many studies consistently resolved two clades but no comprehensive study of mtDNA haplotypes have been made in Africa, the continent in which the species originated.ND4 haplotypes were sequenced in 426 Ae. aegypti s.l. from Senegal, West Africa and Kenya, East Africa. In Senegal 15 and in Kenya 7 new haplotypes were discovered. When added to the 95 published haplotypes and including 6 African Aedes species as outgroups, phylogenetic analyses showed that all but one Senegal haplotype occurred in a basal clade while most East African haplotypes occurred in a second clade arising from the basal clade. Globally distributed haplotypes occurred in both clades demonstrating that populations outside Africa consist of mixtures of mosquitoes from both clades.Populations of Ae. aegypti outside Africa consist of mosquitoes arising from one of two ancestral clades. One clade is basal and primarily associated with West Africa while the second arises from the first and contains primarily mosquitoes from East Africa.